Wiedza, umiejêtnosci, osobowosc i praca trenera - Czajkowski, Z. (Human Movement, 2000)
he author tries in a short, concise manner to present the coach's work, his skills, abilities, ways of choosing how to conduct exercises, the ways he influences his pupils and his leadership style. Coach's skills, knowledge, tasks, and the essence of his work Coach's work is extremely versatile - conducting training, teaching motor skills and tactics, developing pupils' energy, fitness and motor co-ordination, and also developing his pupils' personality. The importance of various skills and abilities of a coach depends to a large degree on where he works. In highly competitive sport the primary emphasis is on achieving high results in competitions. In recreational sport the emphasis is on fun, health, active rest, and keeping up the overall level of fitness. In schools and youth sport centres, the primary object is assessing versatile development of children and youth, ensuring the high level of functional and adaptive possibilities, developing sports enjoyment and giving the pupils a sense of self-confidence and competence. To achieve these objectives, the coach must constantly try to keep his personal fitness, to develop his performance skills, to increase his knowledge of sport, psychology, physiology, methodology, etc. The coach should always strive to influence his pupils positively. Certain coach's skills and methods are the same in all branches of sport and some are different and specific to given branches of sport. In figure skating or acrobatics, for example, the coach's main object is to teach many difficult closed motor skills full of finesse and expression, with precise execution. In track and field events and other sports where physical fitness is of a primary importance, the coach must first develop and master energy skills. In combat sports and games energy abilities and co-ordination serve as a basis for tactics and psychomotor abilities. Here, open motor skills, tactical abilities, speed and accuracy of perception, speed of decision and many qualities of attention are important. One unique coaching philosophy does not exist. Great results are achieved by coaches of different personalities, different temperaments, different methods of training, and different leader styles. There are, however, certain common traits among top coaches: 1. Wide, general and specific knowledge which is constantly improving and widening, applying sports science and other basic subjects. 2. High level of technical skills which ensures a high level and efficacy of practical teaching motor skills. 3. High level of ability to convey the knowledge and practical abilities to pupils and good command of methods of perfecting energy and co--ordination abilities, deep knowledge of methodology. 4. Organizing and leadership abilities. 5. Ability to educate, inspire and motivate the pupils; here the most important is the coach's personal example. 6. An innovative approach, constant perfecting of one's own abilities, seeking new knowledge, watching the changes occurring in sport. 7. Ability to plan, program and organize the process of training, controlling its results, exact and penetrative observation of competitions, application of important principles of training (principle of specificity, transfer of skill, individualization, etc.). Ability to conduct exercises in an interesting and colourful manner, implementing interest and love of their discipline of sport among athletes, documentation of training and competitions. 8. Effectiveness in co-operating with officials, other coaches, schools, psychologists, journalists, etc. 9. Sharing his knowledge and experience with younger coaches and instructors, trying to develop his own branch of sport, publications. Coach's motivation In a coach's professional activities we may distinguish many different motives (rivalry motive, motive of social approval, financial motives, etc.). There are three main groups of motive, however, which we have to distinguish: 1. Achievement of highest possible results by his pupils. 2. Assuring the pupils' feelings of fun and enjoyment, optimal level of arousal, and feelings of competence. 3. Assuring the young athletes' versatile development, education, developing pupils' independence and self-efficacy. Taking care of health, psychological, social, and mental development. Is there one unique, ideal coach profile? The answer to this question is definitely "no". I would suppose that every great coach chooses and walks his own path. Coaches of very different personality and temperament, using quite different methods of training and quite different styles of leadership achieve great results. Great coaches are not devoid of certain weak points. They achieve high results, not because they lack weak points, but because of great development of their strong points and possibilities. One can give many examples of famous coaches who achieved very high results in various branches of sport and whose views and methods were quite different. Generally, it is accepted to assess a coach's quality by his pupils' results in competitions The author expresses the opinion that a great coach is the one who: 1. Ensures his pupils' great results in competition. 2. Properly educates his pupils and develops their personalities. 3. Tries to develop his discipline of sport, introduces new knowledge and new methods. 4. Shares his knowledge and skills with others, teaches younger coaches and instructors, and presents his experience and wisdom in the form of books and articles. In spite of many marked differences between various great coaches, there are certain features and qualities which are common to all of them. 1. Great love of his sport and creative passion. 2. Introducing new knowledge and new methods. 3. Apllying the experience of other sports, but not blindly copying. 4. Strong personality with powerful influence on pupils. 5. Perfect acquisition of the technique of his sport; inspiring demonstrations; interesting and colourful manner of conducting exercises. 6. Self-assurance and self-confidence; belief in the rightness of his views and efficacy of his methods but, at the same time, open approach to other views and methods. 7. The gift to convey his knowledge and abilities to others. 8. Wide, general interest (in spite of great concentration on his own branch of sport, a good coach may be a maniac but not a monomaniac). 9. Great talent in teaching, desire, and ability to convey his knowledge and experience to others, including in the form of books and articles. 10. Great creative energy, perseverance in activity, enthusiasm for work. The variety of different coaches' profiles is reflected, among other things, in different leadership styles. One may distinguish the following leadership styles: 1. Formal style - the coach and athlete co-operate, concentrating on the achievement of consecutive training tasks. 2. Directive style - the coach distinctly plays the part of the superior and leader, he teaches, gives orders, and the athlete listens and follows the orders. 3. Dictatorial style - extreme form of the previous style - the coach behaves like a dictator. He does not explain anything, he does not care about the pupil's opinions or feeling, he gives orders, he applies negative reinforcements, often treating his pupils instrumentally. 4. Co-operative style - it may be applied even with young pupils, the coach directs the process of training but he explains his decisions, he takes into account pupils feeling, doubts, questions, and opinions, he stimulates athletes initiative and independence. 5. Friendly style - may be applied with adult, intelligent athlete; there is friendly co-operation between coach and athlete, and marked emotional linkage. Competition profile and individualization of training The author does not support a very fashionable theory of champion profile. He thinks that, great coaches - like great athletes, Olympic medallists, although they do have many similar traits, may and do differ in many respects. He expresses the opinion that: 1. Training and competitions should not make watertight compartments. An athlete in training must see certain situations which occur in competitions and in a contest he must recollect certain situations experienced during training. 2. In planning and conducting training, we mostly take into account what actually happens in competitions - which actions are most commonly used, which are more efficacious, what style of fencing, etc. is prevalent and more successful, etc. 3. Apart from modelling the training on competition profile, one most take into consideration athlete's personality (introvert, extrovert; emotionally stable or unstable; phlegmatic or choleric; offensive or defensive; slow or fast reaction; etc.). 4. In the long-reaching plan of training, an athlete must cross the following "difficulty thresholds". a) learning a given amount of motor skills, b) transferring these skills from exercise into training bouts or training games, c) transferring skills from training bout or training game into competitions. What one must avoid In their activities, coaches most avoid blind copying of others, cliché action and movement, "functional fixation", failing to notice changes of sport and methods of training. The author gives several practical examples of mistakes coaches should avoid.